Rancang Bangun Sistem Informasi Akademi: Modul Sistem Absensi Berbasis Mobile dan Web pada Universitas Universal - Gulo, Johanes Try Oktavianus; Febrianti, Eka Lia; Simalango, Holong Marisi (Jurnal Informatika Universitas Pamulang, 2020)
The academic information system that focuses on the attendance module is a continuation of the manual attendance that imposes the use of attendance papers that are paraphrased by students. Attendance modules at Universal University can be designed utilizing Internet technology and network, where students only use smartphones to scan Quick-Response Code (QR Code) and web-based applications for lecturers to verify attendance. The attendance module is designed using real-time data processing. The software process Model used is the waterfall model and assisted with analysis using Unified Modelling Language (UML). The design of the application uses the PHP programming language for Web applications and Java for mobile applications, as well as databases using MySQL. The result of the design of the build attendance module in the form of a mobile application for use by students who can scan QR Code as attendance, and a Web application to be used by the lecturer as an attendance verification that has scanned QR Code and students who are not present. Attendance is more effective online when compared to manual attendance.